Unique mutation, accelerated mTOR signaling and angiogenesis in the pulmonary cysts of Birt‐Hogg‐Dubé syndrome. (18th January 2013) - Nishii, Teppei; Tanabe, Mikiko; Tanaka, Reiko; Matsuzawa, Tetsuhiro; Okudela, Koji; Nozawa, Akinori; Nakatani, Yukio; Furuya, Mitsuko
<x xml:space="preserve">Abstract</x> Birt‐Hogg‐Dubé syndrome (BHD) is an autosomal dominant disorder characterized by fibrofolliculomas, renal tumors and pulmonary cysts with repeated pneumothorax. This disorder is caused by mutations in the gene that encodes folliculin (FLCN). FLCN is known to be involved in the signaling of mammalian target of rapamycin (mTOR). We investigated the lung of a BHD patient who presented with a unique mutation. A 33‐year‐old woman visited our hospital due to repeated pneumothorax. Histopathologic study of the resected lung demonstrated multiple epithelial cysts. An increase of blood vessels was observed in the vicinity of subpleural cysts. Genomic DNA analysis revealed heterozygous mutation at the 3′ end of intron 5 of the FLCN gene. Total mRNA and protein were extracted from the resected lung tissue. RT‐PCR and sequence analysis demonstrated the production of exon 6‐skipped FLCN mRNA. In Western blotting, the band intensities of phospho‐mTOR, phospho‐S6, phospho‐Akt, hypoxia‐inducible factor (HIF)‐1α and vascular endothelial growth factor (VEGF) were increased in the BHD lung compared with normal lungs. Histopathologic analysis demonstrated strong immunostainings of mTOR signaling molecules in cyst‐lining cells. Collective data indicates that dysregulation of mTOR signaling facilitates S6‐mediated protein synthesis and HIF‐1α‐mediated angiogenesis, which may contribute to the development of pulmonary cysts in this disorder.